Исследование режимов выделения радиоизотопов йода из облученной мишени на основе Те02; Известия вузов. Физика; Т. 54, № 11(2) - Гарапацкий А. А. Александр Александрович; Головков В. М. Владимир Михайлович; Большаков А. М. Алексей Михайлович; Семенов А. С. Алексей Сергеевич; Скуридин В. С. Виктор Сергеевич; Минин С. М. Станислав Михайлович (2011, 2011)
Заглавие с экрана